Adverse effects of bisphenol a on the liver and its underlying mechanisms: evidence from in vivo and in vitro studies - Abdulhameed, Al-Salihi Ahmed Rashid; Lim, Vuanghao; Bahari, Hasnah; Khoo, Boon Yin; Abdullah, Muhammad Nazrul Hakim; Tan, Jun Jie; Yong, Yoke Keong (Hindawi, 2022)
BPA is a known endocrine-disrupting agent that is capable of binding to the estrogen receptor and has exhibited adverse effects in many laboratory animal and in vitro studies. Moreover, it also been shown to have estrogenic, antiandrogenic, inflammatory, and oxidative properties. The widespread presence of BPA in the environment presents a considerable threat to humans. BPA has been shown to be leached into the human ecosystem, where it is commonly found in food products consumed by humans. Although the concentration is relatively low, its prolonged consumption may cause a variety of deleterious health effects. The liver is an important organ for metabolizing and detoxifying toxic metabolites to protect organisms from potentially toxic chemical insults. BPA that is ingested will be eliminated by the liver. However, it has also induced hepatoxicity and injury via various mechanisms. To find research demonstrating the effects of BPA on kidney, a number of databases, including Google Scholar, MEDLINE, PubMed, and the Directory of Open Access Journals, were searched. Thus, this review summarizes the research on the relationship between BPA and its effects on the liver-derived from animals and cellular studies. The underlying mechanism of liver injury caused by BPA is also elucidated.